EVALUASI PENERAPAN SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) DALAM PELAKSANAAN LAPORAN KEUANGAN PADA DINAS KESEHATAN KABUPATEN PONOROGO - Della Ameliya Putri; Tsania Nur Alifah, Titis Purwaningrum (JOURNAL OF COMMUNITY DEDICATION, 2024)
The purpose of this study is to evaluate the implementation of the Regional Government Information System (SIPD) in the preparation and execution of financial reports at the Health Office of Ponorogo Regency. The SIPD is a system designed to increase transparency, accountability, and efficiency in financial management within regional governments. A variety of methods were used to collect data. Nonetheless, a number of obstacles still exist, including the scarcity of skilled human capital and technological problems with system operation. To maximize the system's deployment, the report suggests bolstering technological infrastructure and expanding training for SIPD users. It is intended that this study will help other regional governments handle their financial reports better by providing guidelines.